Hanging out : the radical power of killing time - Liming, Sheila (Melville House, 2023)
"Starting with the assumption that play is to children as hanging out is to adults, Liming makes a brilliant case for the necessity of unstructured social time as a key element of our cultural vitality. The book asks questions like what is hanging out? why is it important? why do we do it? how do we do it? and examines the various ways we hang out--in groups, online, at parties, at work." -- Amazon.